Solubilisation des hydrocarbures dans les solutions micellaires Influence de la structure et de la masse moléculaire Solubilization of Hydrocarbons in Micellar Solutions Influence of Structure and Molecular Weight - Baviere M.; Rouaud T. (Oil & Gas Science and Technology, 2006)
La solubilisation des hydrocarbures par les solutions de tensio-actifs utilisés pour la récupération améliorée du pétrole est directement liée à l'efficacité interfaciale de ces solutions. D'autant plus élevée que la tension interfaciale entre la phase micellaire et l'huile est plus basse, elle dépend fortement de la nature de l'hydrocarbure. Dans certains cas, celui-ci est responsable de comportements de phase inhabituels. On examine d'abord dans cet article la méthodologie généralement utilisée pour caractériser les propriétés interfaciales des mélanges eau-huile-tensio-actifs. Elle est fondée, à partir des travaux de Winsor et de quelques auteurs après lui, sur le concept d'énergies de cohésion entre les diverses entités moléculaires présentes et sur le rapport entre ces énergies. Cette approche permet d'orienter le choix des paramètres pour optimiser les formulations du point de vue de la solubilisation et de la tension interfaciale. Les comportements de phase d'hydrocarbures modèles, alcanes et alkylbenzènes, sont ensuite comparés et discutés, ainsi que ceux d'huiles brutes de stockage. Il apparaît notamment que, dans les mélanges d'hydrocarbures, le paramètre d'optimisation (ici la masse moléculaire du tensio-actif) varie de façon non linéaire avec les proportions du mélange. Les performances obtenues avec les huiles brutes de masses moléculaires voisines dépendent sensiblement de la composition. Cependant l'influence propre de la structure et de la masse moléculaire des différentes espèces n'a pas encore été établie. A cet égard l'huile de Daqing constitue un cas intéressant : la solubilisation est extrêmement faible, bien que les tensions interfaciales soient relativement basses. D'après des essais préliminaires de fractionnement de ce brut, les résines pourraient être à l'origine de ce comportement. La poursuite des travaux vise à préciser l'effet des fractions lourdes des bruts (paraffines, résines, asphaltènes) sur les propriétés interfaciales, d'une part avec le brut de Daqing, pour effectuer des essais complémentaires, d'autre part avec des constituants modèles en solution dans un solvant approprié. Optimizing the formulation of micellar surfactant solutions used for enhanced oil recovery consists in obtaining interfacial tensions that are as low as possible in multiphase systems resulting from the mixing of the injected solution with formation fluids. The solubilization of hydrocarbons by the micellar phases of such systems is linked directly to the interfacial efficiency of surfactants. Indeed, as has been shown by numerous research projects such as the one by Reed and Healy [1], the amount of hydrocarbons solubilized by the surfactant is all the greater as the interfacial tension between the micellar phase and the hydrocarbons is low. This solubilization depends in particular, although to a great extent, on the nature of the hydrocarbons or, for the processes we are concerned with here, of the hydrocarbon mixtures encountered [181. Likewise, the criteria generally used in applying the process to a reservoir may also be fulfilled (temperature, salinity of the water, viscosity of the oil, nature and permeability of the rock), whereas the chemical nature of the oil turns out to be responsible for very mediocre efficiency. Hence this insufficiency of criteria is revealed for relatively heavy oils such as the oil in the Daqing field in China, for which production may still depend on this recovery method, a priori. The solubilization of this oil by the surfactants normally used is extremely reduced and may perhaps even by almost nil. This particularly unfavorable behavior has brought out the need of specifying selection criteria for fields from the standpoint of the nature of the oil, so as to be able to assess the quality of a crude oil and to detect possible difficulties in applying the process-diff iculties linked to the composition of the oil. Such research must result in the adapting of procedures, in searching for solutions and in setting limits to the process from this standpoint. This article describes the methodology and preliminary results leading to the comparing of the phase behavior of mixtures containing model hydrocarbons having different structures, normal alkanes and alkylbenzenes or stock-tank crudes. The methodology is based on the correlations worked out by Reed and Healy [1] between the, existence of low interfacial tensions and the obtaining of a phase diagram having a specific configuration said to be of the Winsor Type III [7]. In this configuration, the multiphase zone contains, in particular, a three-phase domain in which an intermediate micellar phase is in equilibrium with an aqueous phase and a hydrocarbon phase. When the affinity of the surfactant for the water and the hydrocarbon is the same, the micellar phase contains equal amounts of water and hydrocarbon. The system is then considered, by convention to be an optimal one. In mixtures of water, amphiphilic compounds (surfactant and alcohol) and hydrocarbons having different molecular weights and structures, the solubilizing power is measured at the reference point obtained by adjusting the molecular weight of the surfactant. However, all optimal systems are not equivalent. Solubilization is all the greater and hence the lowering of the interfacial tension is all the more marked as the energies of cohesion between the surfactant and the water and hydrocarbon are strong. This approach is fruitful for interpreting performance variations when some parameters of the system are modified, such as the molecular weight and structure of the hydrocarbon or the salinity of the water. During this study, we show that the optimal molecular weight of the surfactant varies linearly with that of the pure hydrocarbon (alkane or alkylbenzene), at least within the range of molecular weights examined here. Solubilization also varies linearly. This ideal behavior disappears for hydrocarbon mixtures. The different effects of alcohol on the phase behavior of micellar systems, due to its partitioning among the different phases, have been confirmed, and in particular the effect on solubilization. This solubilization is all the weaker as the alcohol concentration is great. The solubilization of crude oils depends strongly on their chemical composition. It may vary from single to double for crudes having exactly the same equivalent alkane, i. e. having similar molecular weights. Oil from Daqing has very weak solubilization, even though the interfacial tensions between the micellar phase and the excess oil are relatively low. According to tests of fractions extracted from the crude oil, resins might be responsible for such a behavior in an environment with high molecular weights. To achieve better control over the formulation of micellar fluids, further research will have to be done to determine the effect of heavy constituents (paraffins, resins and asphaltenes) on the interfacial properties of water/hydrocarbon/surfactant systems. Likewise, the interactions occurring between the hydrocarbon constituents and the surfactant raise problems concerning the choice of the surfactant. The use of surfactants having varying structures, mainly with regard to the lipophilic part (branching, aromaticity, etc). , should make it possible to indicate to what extent this structure can be adapted to the composition of the oil to make formulations as efficient as possible.